The Influence of Local Government Expenditure Realization and Investment on The Poverty Rate in Nabire Regency - Rosang, Romario Estevan; Maramis, Mauna Th. B.; Kawung, George M.V. (Journal Research of Social Science, Economics, and Management, 2025)
The poverty rate is one of the main indicators for measuring the success of a region’s economic development. Despite the implementation of various poverty alleviation programs, poverty remains a serious challenge, particularly in areas with limited resources and infrastructure, such as Nabire Regency. This study aims to analyze the effect of regional government expenditure and investment on the poverty rate in Nabire Regency. The data used are secondary data covering the period from 2012 to 2023. The analytical method employed is multiple regression analysis using Eviews 12. The results of the study show that regional government expenditure has a negative and significant effect on the poverty rate, indicating that increased government expenditure can reduce poverty. On the other hand, investment has a negative but not significant effect on the poverty rate, suggesting that incoming investments have not yet had a direct impact on poverty reduction. Nevertheless, both government expenditure and investment simultaneously have an influence on the poverty rate in Nabire Regency. The findings emphasize the crucial role of government expenditure in poverty reduction and highlight the need for more targeted investment policies that can directly benefit the poor population.